Towards non-blinking and photostable perovskite quantum dots - Chenjia Mi; Gavin C. Gee; Chance W. Lander; Donghoon Shin; Matthew L. Atteberry; Novruz G. Akhmedov; Lamia Hidayatova; Jesse D. DiCenso; Wai Tak Yip; Bin Chen; Yihan Shao; Yitong Dong (Nature Communications)
Abstract Surface defect-induced photoluminescence blinking and photodarkening are ubiquitous in lead halide perovskite quantum dots. Despite efforts to stabilize the surface by chemically engineering ligand binding moieties, blinking accompanied by photodegradation still poses barriers to implementing perovskite quantum dots in quantum emitters. To date, ligand tail engineering in the solid state has rarely been explored for perovskite quantum dots. We posit that attractive intermolecular interactions between low-steric ligand tails, such as π-π stacking, can promote the formation of a nearly epitaxial ligand layer that significantly reduces the quantum dot surface energy. Here, we show that single CsPbBr3 quantum dots covered by stacked phenethylammonium ligands exhibit nearly non-blinking single photon emission with high purity (~ 98%) and extraordinary photostability (12 hours continuous operation and saturated excitations), allowing the determination of size-dependent exciton radiative rates and emission line widths of CsPbBr3 quantum dots at the single particle level.